Sanctifying Slavery and Politics in South Carolina : The Life of the Reverend Alexander Garden, 1685-1756 - Witzig, Fred E. (Book collections on Project MUSE., 2018)
"When Alexander Garden, a Scottish minister of the Church of England, arrived in South Carolina in 1720, he found a colony smoldering from the devastation of the Yamasee War and still suffering from economic upheaval, political factionalism, and rampant disease. It was also a colony turning enthusiastically toward plantation agriculture, made possible by African slave labor. In Sanctifying Slavery and Politics in South Carolina, the first published biography of Garden, Fred E. Witzig paints a vivid portrait of the religious leader and the South Carolina colony he helped shape"--